Etnografia di un reparto psichiatrico: Per un ripensamento dell’antropologia come scienza responsabile - Dolce, Chiara (Antropologia Pubblica, 2024)
Anthropology is overall a scientific and unethical system. However its scientific nature can not ignore the ethical tension proper to man, in whose nature is already inscribed the judgment on himself and on the world, where every judgment, as the etymology suggests, is "pronunciation of judgment" towards what is judged, therefore implying an act of responsibility. Just with this assumption of responsibility I had to deal in the summer 2013, when I observed some patients at the psychiatric ward of the Civil Hospital of Sassari, determined to grasp concretely the nature of the human person from the theory of Ernesto de Martino. The clash between theory and practice that has occurred as a result of this observation, generated from my dissent to recognize the mental patient as a non-person and at the same time, paradoxically, from my full recognition of madness as non-value, after some time has become an opportunity for a critical rethinking of anthropological science and its methods, in order to prevent any damage against the subject of research and to stimulate a more responsible participation in the integral knowledge of the human being.